(untitled) (Revista Lusófona de Educação, 2026)
Between motivation and knowledge: a systematic review of game-based learning in school education Abstract: Play, in its multiple forms, has been recognised as an effective didactic tool to enhance learning in educational contexts. In recent years, its integration in the classroom through methodologies such as Game-Based Learning (GBL) has gained special relevance in primary and secondary education. This article presents a systematic review of recent studies that analyse the impact of GBL on the educational process. The results show that the use of games, both traditional and digital, contributes to improving motivation, active student participation and the development of various key competences. Moreover, common elements are identified in the successful experiences, such as the adapted pedagogical design, the contextualisation of the contents and the involvement of teachers. Despite the benefits observed, there are still some challenges related to the practical implementation and assessment of learning. Among the conclusions, we highlight the positive impact of GBL on academic performance and the promotion of transversal skills such as cooperation, critical thinking and problem solving, as well as the importance of careful didactic planning to maximise its effects. Keywords: Early childhood; Gamification; Game-based learning; Systematic literature review.